Perceptions and experiences with two no-test direct-to-patient telehealth medication abortion regimens in the USA: an exploratory study with mifepristone and misoprostol and misoprostol-only regimens - Dana Johnson; Laura Fix; Terri-Ann Thompson; Melissa Grant; Ibtehal Jastaniah (BMJ Publishing Group, 2024)
Introduction Telehealth medication abortion (teleMAB) is an option for expanding abortion access in the USA. In this study, we compared the accessibility of two no-test, direct-to-patient teleMAB regimens: mifepristone and misoprostol, and misoprostol-only.Research design and methods Over a 5-month period, we conducted an exploratory study surveying clients who received teleMAB services from an abortion clinic offering teleMAB. We calculated descriptive statistics focusing on the healthcare access dimensions of acceptability and accommodation. We conducted a content analysis of open-response comments focusing on convenience.Results Of the 218 clients in the study: 195 (89%) selected the mifepristone and misoprostol regimen and 23 (11%) selected the misoprostol-only regimen. Across all respondents, 88% reported they would use the service again if they needed an abortion in the future. Half of the respondents (52%) connected to the service using a smartphone, 99% owned the device that they used, 98% could easily hear and 99% could easily talk to the prescribing provider, and only 7% had a problem connecting to the service. Respondents felt that teleMAB was convenient because they had quality and trustworthy communications. It also accommodated their childcare needs, travel, and scheduling, felt private and comfortable, and facilitated a sense of reproductive autonomy.Conclusions Respondents found both teleMAB regimens to be acceptable, technologically accommodating and convenient. These results have promising implications for states positioned to expand insurance coverage and reimbursement for teleMAB, including misoprostol-only regimens. Results also inform a need to focus on policies that expand access to teleMAB through nationwide internet connectivity.